“Something Intended, Complete”: Yeats and the Remodelled Self - O’Neill, Michael (Romanticism and Victorianism on the Net, 2008)
AbstractThe essay examines Yeats’s highly self-conscious representation of the self in the light of his assertion in A General Introduction for My Work that, in a poem, the poet is remodelled as “something intended, complete.” It pays particular attention to a range of individual poems across his career, doing so in order to explore the idea that it is in the unfoldings of the poetry itself that we can encounter most closely and fruitfully the conflicting tensions associated with Yeats’s post-Romantic remodelling of the self. The poems are shown to derive much of their power and value from the ways in which they enact, work through, and dramatise the crisscrossing strains associated with the proposition quoted from A General Introduction.